If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(r + 4) = 24 Reorder the terms: -2(4 + r) = 24 (4 * -2 + r * -2) = 24 (-8 + -2r) = 24 Solving -8 + -2r = 24 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -2r = 24 + 8 Combine like terms: -8 + 8 = 0 0 + -2r = 24 + 8 -2r = 24 + 8 Combine like terms: 24 + 8 = 32 -2r = 32 Divide each side by '-2'. r = -16 Simplifying r = -16
| 3(a-4)+15=13 | | 12p=15 | | 4(x-6)+14(x+10)= | | 129=15 | | 240=(5*w*2)+(w*2) | | 89=0.9d+71 | | 408b=36 | | (3/10)*(5/3) | | 5(5x+7)-12x= | | 8.1=-7a+2.1 | | M-11=43 | | x^2+7+9=3 | | f(-4)=9x+8 | | 9-(2y-3)=1-3y | | y-7=-1/2(x-4) | | (3x-9i)(x-3i)=0 | | 7(4y+5)=19y+8 | | 2y+y+9y= | | 15y=6y^2 | | a+1+a+3+2a=180 | | 1+3s=4 | | a+1+a+3+2a=90 | | x*y=31 | | 16f=1.8+32 | | c=2a+3 | | m/36=2 | | dxy=31 | | F(x)=-2x^2-5x+7 | | 7(x+5)+5=9x-2(x-4) | | 70=6p+34 | | 16=2a+5 | | 3x+5+6x-9=-4 |